Ability to Write Explanatory Text in Grade VI Elementary School Students Using Picture Media - Nena Purnamawati; Prana Dwija Iswara; Yana Erlita Hakim (International Conference on Elementary Education, 2023)
The ability to write explanatory text is a process of expressing ideas and thoughts written in the form of sentences based on facts and phenomena that occur so that the reader knows the information. The purpose of this study was to describe students' ability to write explanatory texts in grade VI elementary school students using the aid of media images, explain students' obstacles in writing explanatory texts and find solutions given to overcome students who are less able to write explanatory texts. The type of method used in this research is to use a descriptive method with a quantitative approach. The sample of class VI Elementary School students is 32 people. The research technique is by tests, observations, and interviews. The assessment guide includes aspects of the suitability of the theme with the content, text structure, use of language, and punctuation. Based on the research results obtained an average of 69.75. The suitability of the theme with content is 18.28, text structure is 21.00, language use is 15.24, and punctuation is 15.23. The lowest score is in the use of language and punctuation. Students still do not understand the use of punctuation marks in a sentence, and the use of language is not yet structured, because students lack confidence, lack knowledge, and language in making an essay. Requires varied methods, writing experience, and literate culture to stimulate students in writing.